Influence of excess sodium and phosphorus on the ionic conductivity of NASICON-structured Na3Zr2(SiO4)2PO4 ceramic solid electrolyte - Chong M.K.; Zainuddin Z.; Omar F.S.; Jumali M.H.H.; Ansari M.N.M. (Elsevier Ltd, 2025)
NASICON-structured Na3Zr2(SiO4)2PO4 (NZSP) is regarded as one of the most promising solid-state electrolytes (SSEs) for all-solid-state Na-ion batteries mainly due to its high thermal stability and wide electrochemical window. However, the existing NZSP tends to exhibit lower ionic conductivity at room temperature. Thus, in order to solve this issue, NaH2PO4 was chosen as a novel phosphate source for the synthesis of NZSP via solid-state reaction method. On top of that, excess sodium (Na) and phosphorus (P) were also added into parent NZSP SSE with different weight percentage ratios to investigate their effects on Na+ ion activation energy. Structural study reveals NZSP with either excess Na or P have the same crystal structure morphology but are dissimilar in terms of the presence of impurities and grain size. NZSP with the excess of Na shows the highest ionic conductivity (1.05 ? 10?3 S cm?1) and electrode polarization contributed by the increasing of Na+ carriers and the excess Na+ ion vacancies. These results authenticate that the excess of Na can be an effective way to improve the performance of NZSP SSE for energy storage application. ? 2024 Elsevier Ltd